Examining the Impact of Authentic Leadership and Organizational Culture on Organizational Commitment in Universities: A Structural Equation Modeling Approach - Novitasari, Dewiana; Utami, Heryanti; Purnawan, Julius; Choirida; Amiruddin, Ja'far (IJOSMAS, 2024)
This research uses Partial Least Squares Structural Equation Modeling (PLS SEM) using SmartPLS software to analyze the relationship between authentic leadership, organizational culture, and organizational commitment in a university context. Focusing on the influence of deans and directors at Indonesian universities, this research investigates how authentic leadership impacts organizational culture and subsequently influences the commitment of university lecturers. Through a survey involving 350 lecturers from several universities in Indonesia, this research reveals the dynamics between these variables. The results highlight the important role of authentic leadership in establishing a positive organizational culture that, in turn, increases organizational commitment among university faculty. This study also found that organizational culture is able to be a mediator that strengthens the relationship between authentic leadership and organizational commitment. The implications for sustainable organizational development and future research pathways are discussed in terms of these key variables using the PLS SEM methodology with SmartPLS software.